2020
DOI: 10.1016/j.ebiom.2020.102650
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule inhibitor of PCSK9 transcription ameliorates atherosclerosis through the modulation of FoxO1/3 and HNF1α

Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secreted protein that down-regulates hepatic low-density lipoprotein receptor (LDLR) by binding and shuttling LDLR to lysosomes for degradation. The development of therapy that inhibits PCSK9 has attracted considerable attention for the management of cardiovascular disease risk. However, only monoclonal antibodies of PCSK9 have reached the clinic use. Oral administration of small-molecule transcriptional inhibitors has the potential to beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…To investigate whether pterostilbene regulated PCSK9 promoter activity as previously described [ 31 ], we amplified the human PCSK9 gene promoter by polymerase chain reaction (PCR), with HL-1 genomic DNA serving as our template, to generate pGL3-Basic vector clones (Promega, Madison, WI, USA) at the Xho I and Hind III sites, resulting in the pGL3-PCSK9-P plasmid, which was used as a template for PCR amplification of the PCSK9 gene promoter fragments (P1–P6) ( Figure 4 A). Using the constructed luciferase reporter plasmid containing fragments of the 5′ flanking 1455-bp promoter region (P1–P6) of PCSK9, the initial post-transfection amplification of PCSK9 promoter-luciferase activity (10-fold, p < 0.01) in HL-1 cardiomyocytes was significantly and dose-dependently suppressed after treatment with 2.5 (5.04-fold, 5.04-fold, p < 0.01) and 5 μM (2.85-fold, p < 0.01) pterostilbene as shown in Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether pterostilbene regulated PCSK9 promoter activity as previously described [ 31 ], we amplified the human PCSK9 gene promoter by polymerase chain reaction (PCR), with HL-1 genomic DNA serving as our template, to generate pGL3-Basic vector clones (Promega, Madison, WI, USA) at the Xho I and Hind III sites, resulting in the pGL3-PCSK9-P plasmid, which was used as a template for PCR amplification of the PCSK9 gene promoter fragments (P1–P6) ( Figure 4 A). Using the constructed luciferase reporter plasmid containing fragments of the 5′ flanking 1455-bp promoter region (P1–P6) of PCSK9, the initial post-transfection amplification of PCSK9 promoter-luciferase activity (10-fold, p < 0.01) in HL-1 cardiomyocytes was significantly and dose-dependently suppressed after treatment with 2.5 (5.04-fold, 5.04-fold, p < 0.01) and 5 μM (2.85-fold, p < 0.01) pterostilbene as shown in Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
“…Transfection of reported plasmids and the establishment of stable PCSK9 promoter –cells, and the luciferase report assay were conducted strictly following already established protocols [ 31 ] and according to the reagent manufacturers’ instructions. Transfected cells were then treated with DMSO- or pterostilbene for 24 h. Luciferase activity was evaluated using the Luciferase Reporter Assay System (#E1500; Promega) and all the luminescence was Renilla luciferase activity-normalized.…”
Section: Methodsmentioning
confidence: 99%
“…The protective effects of atorvastatin and PCSK9 inhibitor are likely to be through the same mechanisms. Previous studies reported that PCSK9 inhibitor and atorvastatin could effectively reduce LDL levels in obese rats 47,48 . In addition, it has been shown that PCSK9 inhibitor effectively reduced inflammatory markers including the number of monocytes adhering and the number of T cells in the aortic root area in atherosclerotic model rats 49 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reported that PCSK9 inhibitor and atorvastatin could effectively reduce LDL levels in obese rats. 47,48 In addition, it has been shown that PCSK9 inhibitor effectively reduced inflammatory markers including the number of monocytes adhering and the number of T cells in the aortic root area in atherosclerotic model rats. 49 Also, atorvastatin could reduce inflammation in the heart as indicated by increased AMPK activity and decreased NF-κB activity in obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Huh7 cells), Pinostrobin (HepG2 cells), and tanshinone IIA (HepG2 cells) reduce PCSK9 expression in a FoxO3a-dependent manner, probably via attenuating HNF1α-mediated activation of PCSK9 expression and/or methylation in the promoter region of PCSK9 (79-82). A small molecular, 7030B-C5, also reduces PCSK9 expression in HepG2 cells and mice mainly through the FoxO1 and HNF1α pathway (83). In addition, Berberine reduces PCSK9 expression mainly through attenuating SREBP2 and HNF1α-mediated upregulation of PCSK9 transcription in HepG2 cells (73), which may account for its cholesterol-lowering effect.…”
Section: Regulation Of Pcsk9 Expressionmentioning
confidence: 99%